Homoleptic uranium and lanthanide phosphinodiboranates. Issue 44 (16th May 2018) - Blake, Anastasia V.; Fetrow, Taylor V.; Theiler, Zachary J.; Vlaisavljevich, Bess; Daly, Scott R.
Abstract : The synthesis and structures of a new class of homoleptic f-metal borohydride complexes (phosphinodiboranates) are described with U, Nd, and Er. Abstract : Here we report a new class of homoleptic f-element borohydride complexes called phosphinodiboranates. Treating UI3 (1, 4-dioxane)1.5, NdI3, or ErI3, with three equiv. of K(H3 BP t Bu2 BH3 ) in Et2 O yielded M2 (H3 BP t Bu2 BH3 )6, where M = U, Nd, and Er. All three complexes form solid-state dimers, but exist as mixtures of monomers and dimers in solution.